Ciclosporin Therapy After Infliximab Failure in Hospitalized Patients With Acute Severe Colitis is Effective and Safe. (6th February 2019) - Weisshof, Roni; Ollech, Jacob E; El Jurdi, Katia; Yvellez, Olivia V; Cohen, Russell D; Sakuraba, Atsushi; Dalal, Sushila; Pekow, Joel; Rubin, David T
Abstract: Background and Aims: Options for medical management of patients with acute severe colitis [ASC] failing intravenous (i.v.) steroids are limited and include rescue therapy with either infliximab or ciclosporin. In patients failing infliximab, second-line rescue therapy with ciclosporin is an alternative. The aim of this study was to investigate the efficacy and safety of ciclosporin in patients with steroid-refractory ASC failing first-line rescue therapy with infliximab. Methods: This is a retrospective, tertiary centre study undertaken from 2010 to 2017. Included were patients hospitalized for ASC and treated with i.v. ciclosporin after failing i.v. steroids and infliximab within the previous 2 months. Time to colectomy, clinical response, and occurrence of adverse events were analysed. Results: Forty patients with steroid-resistant ASC were included. Patients were followed for a median of 13 months (interquartile range [IQR] 5–32 months). Colectomy-free survival was 65%, 59.4%, and 41.8% at 1 month, 3 months and 1 year, respectively. Sixty percent of patients [24/40] achieved clinical remission at a median of 2 weeks [IQR 1–3 weeks]. Infliximab levels before ciclosporin infusion were available for 26 patients [median level 17.5 mg/mL, IQR 8–34 mg/mL] and were not associated with adverse events. Sixteen patients [40%] experienced adverse events after ciclosporin treatment, but none resulted in drug discontinuation. Conclusions: In patients with i.v. steroid–refractory ASC who failed infliximab therapy, second-line rescue therapy with ciclosporin was shown to be effective and safe. This is the largest patient cohort to receive ciclosporin as second-line rescue therapy for ASC. We believe that ciclosporin may be offered to selected patients prior to referral for colectomy.